Nuclear Energy for Everyone, Nuclear Weapons for No-One - Makarim Wibisono (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2016)
The article explores the complicated nature of non-proliferation of nuclear weapons even though from the military, ethical and legal perspective, the destructiveness, immorality and illegality of the current situation cannot be perpetuated. Some of the nuclear-weapon states, however, have consistently refused to agree to any approach under multilateral auspices for the abolition of nuclear weapons. Rather, attention has been deflected to the horizontal proliferation of nuclear weapons, while the equally urgent task of complying with the legal obligation of implementing Article VI of the Non-Proliferation Treaty (NPT) concerning nuclear disarmament has been marginalized. I argue, no form of warfare would confront humanity with dangers even remotely comparable with the danger of nuclear warfare. Such disaster would affect the world economy and other vital aspects of the global infrastructure. The sudden collapse of many of the world’s leading trading nations as well as the mechanisms for international transactions would lead to profound disorganization and leave other nation. In addition to the human cost, the ecology of the world would be severely affected and the infrastructure of civilization would be shattered.